2020
DOI: 10.18632/aging.103525
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire assessment helps the self-management of patients with inflammatory bowel disease during the outbreak of Coronavirus Disease 2019

Abstract: Objective: This study aimed to assess the disease conditions of patients with inflammatory bowel disease (IBD) in Hubei Province during the outbreak of Coronavirus Disease 2019 (COVID-19) by questionnaire online and guide their self-management during this epidemic. Results: A total of 102 eligible questionnaires were included. No patient we surveyed reported a diagnosis of COVID-19. Our result showed that 67.86% of patients with ulcerative colitis (UC) and 80.43% of patients with Crohn's disease (CD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
(20 reference statements)
4
12
0
Order By: Relevance
“…In our study, while active IBD disease significantly affected psychological distress, somatization symptoms, and HRQL (as expected), the pandemic-related living condition played unexpectedly only a negligible role in the association with HRQL. Consistent with one of the few previous investigations ( 23 ), self-isolation during the Covid-19 outbreak seems to be less linked with impaired HRQL than the clinical condition (particularly disease activity) and psychological distress of the patients. This is an interesting result, given that being in isolation could decrease the discomfort causing by the management of the symptomatology and the fear of contracting Covid-19 in these patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, while active IBD disease significantly affected psychological distress, somatization symptoms, and HRQL (as expected), the pandemic-related living condition played unexpectedly only a negligible role in the association with HRQL. Consistent with one of the few previous investigations ( 23 ), self-isolation during the Covid-19 outbreak seems to be less linked with impaired HRQL than the clinical condition (particularly disease activity) and psychological distress of the patients. This is an interesting result, given that being in isolation could decrease the discomfort causing by the management of the symptomatology and the fear of contracting Covid-19 in these patients.…”
Section: Discussionsupporting
confidence: 90%
“…The present preliminary cross-sectional study aimed to investigate the extent to which HRQL of IBD patients might be influenced by the outbreak of Covid-19 while controlling for disease activity. Based on earlier findings (14,18,19,23), we expected that disease activity would be associated with psychological distress and probably the stressful stay-athome period and that the pandemic outbreak could represent an additional independent factor of psychological distress affecting HRQL.…”
Section: Introductionmentioning
confidence: 99%
“…There was no difference between the 10-item IBD-disk variables pre- and post- pandemic, and so it was concluded that the current COVID-19 pandemic did not impact on disability [ 32 ]. In Hubei Province, in China, 102 patients participated in a cross-sectional study, of which 85% reported a good QoL (measured by the SIBDQ) and 15% a poor QoL [ 33 ]. In another immune-mediated disease, the impact of COVID-19 on HRQoL was also assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in remission however, report a good quality of life. Similarly, Yu et al found a good health-related quality of life in up to 85% of IBD patients (67–80% in remission) during the first wave of the COVID-19 pandemic [ 51 ]. Our IBD-affected children experienced a reduction in their quality of life during the COVID-19 pandemic, especially regarding emotional and social functioning as well as general well-being, assessed by IMPACT III.…”
Section: Discussionmentioning
confidence: 99%